2023
DOI: 10.1097/ta.0000000000003939
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartmental traumatic injury induces sex-specific alterations in the gut microbiome

Abstract: Severe traumatic injury in a rodent model alters the intestinal microbiome in a sex-specific manner. Females have increased diversity and unique microbial signatures compared to males. These sex-specific gut dysbiosis arrays may influence outcomes after multicompartmental trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…Gut bacterial and fungal microbiome profiles were measured and analyzed as per our previously described methods. 96 The fecal samples were preserved at −80°C until microbial DNA extraction. The QIAmp PowerFecal Pro DNA Kit (Qiagen) was used to extract genomic DNA from a 200 mg fecal specimen, following the manufacturer’s guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Gut bacterial and fungal microbiome profiles were measured and analyzed as per our previously described methods. 96 The fecal samples were preserved at −80°C until microbial DNA extraction. The QIAmp PowerFecal Pro DNA Kit (Qiagen) was used to extract genomic DNA from a 200 mg fecal specimen, following the manufacturer’s guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This study also demonstrated shifts in beta-diversity in both PT and PT/CS at days three and seven, with unique microbial composition differences between these groups at each time point [ 82 ]. A shorter-term study of the same polytrauma model in both males and females demonstrated that at baseline pre-injury, females had a higher Shannon index (alpha-diversity) than males and after injury, females and males had similar alpha-diversity [ 83 ]. This study also showed that males and females subjected to polytrauma demonstrated differences in beta-diversity 2 days postinjury, in addition to unique microbiome compositions [ 83 ].…”
Section: Traumamentioning
confidence: 99%
“…A shorter-term study of the same polytrauma model in both males and females demonstrated that at baseline pre-injury, females had a higher Shannon index (alpha-diversity) than males and after injury, females and males had similar alpha-diversity [ 83 ]. This study also showed that males and females subjected to polytrauma demonstrated differences in beta-diversity 2 days postinjury, in addition to unique microbiome compositions [ 83 ]. The evidence in these studies shows the impact of polytrauma on the intestinal microbiome and also underscores the need for more studies investigating the role of sex in the development of the pathobiome and the need to uncover the underlying mechanisms behind postinjury dysbiosis.…”
Section: Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma, of whatever cause, either a clean surgical wound or a severe traumatic injury, leads to an alteration in the beta diversity of resident microbiota due to the oxidative stress caused by both tissue injury and anesthesia. The alteration of the microbiota involves both the intestinal microbiota-being the most studied and definitely considered as a generalized reaction-and the local microbiota, in this case, that of the skin [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%